Medical ethics and doctor's fee - Petrosino, Luigi M. (Medicina e Morale, 1993)
Starting with an observation of the present complexity of the physician-patient relationship, the study concentrates on the doctor's fee. The Author looks into the following questions: what the socio-economic impact of the fee is; what psychological effect it has on the people involved, and finally, where il stands within ethical and religious limits. The study presents the possible solutions from two points of view: on one hand referring to professional deontology with an analysis of specific documents on the subject; on the other hand the ethical perspective.